Strengthening Community Digital Transformation in the New Normal Era - Dandi Yohananda Saputra Utama; Mustika Ningrum; Ranto Siswanto (Transactions on Informatics and Data Science, 2025)
The Community Service Program (PKM) aims to improve digital literacy and accelerate digital transformation in the new normal by strengthening the capacity of village officials and community members to effectively use digital technology in their daily activities. The program was implemented in 2022 in Wanasari Village, through participatory, educational, and practical approaches that actively involved local stakeholders throughout the implementation process. The program consisted of several stages, including preparation, needs assessment, socialization, hands-on training, mentoring, and evaluation to ensure that participants acquired both theoretical knowledge and practical digital skills. The activities focused on optimizing digital-based public services, introducing collaboration applications to support work, education, and communication, and improving village administrative management through simple digital systems. During the mentoring phase, participants received continuous guidance to enhance their confidence and ability to apply digital tools in real-life situations. The results indicated a significant improvement in participants' understanding and competence in using digital technologies. Village officials became more capable of delivering efficient and transparent administrative services, while community members successfully adopted digital collaboration platforms for communication and productivity. Village administrative records became more organized and accessible through digital management. The program contributed positively to sustainable community digital transformation and strengthened digital readiness for future development.